A case of 18 years disease-free survival after combined pancreatoduodenectomy and hemicolectomy for carcinosarcoma of the transverse colon - Susumu Ohwada; Amika Moro; Nair Amit; Kazunari Sasaki; Shinji Sakurai; Atsuko Takada-Owada; Masaru Izumi; Yuhei Nakano; Yasushige Kashima; Hideki Matsuyama (Surgical Case Reports, 2021)
Abstract Background Ascertaining the origin of large tumors located in the region of the pancreas head and adjacent mesocolon can pose a challenge preoperatively. En bloc pancreatoduodenectomy with hemicolectomy is often required towards curative tumor resection (R0) of malignant tumors in this region. Case presentation Herein we report a case of a 48-year-old man with two contiguous masses each 5 cm in size, located in the pancreatic head. The masses were detected incidentally by abdominal ultrasonography at an annual health check. Endoscopic biopsies revealed inflammation with no malignancy. Cross-sectional imaging showed the tumor direct invasion of the uncinate process of the pancreas, and the third portion of the duodenum. Based on imaging, a malignant submucosal tumor originating from mesenchymal cells in the mesentery of the transverse colon was made preoperatively. The mass required en bloc pancreatoduodenectomy, right hemicolectomy, and resection of the superior mesenteric vein. The final pathology was carcinosarcoma of the transverse colon. The patient survived 18 years after surgery without recurrence. Conclusions Malignant tumors located in the region of the pancreas head should be considered for an en bloc curative tumor resection and adjuvant chemotherapy treatments offered that might be beneficial for carcinosarcoma.